Pengaruh Perilaku Entrepreneur dan Keaktifan Berorganisasi Terhadap Kesiapan Kerja Dimoderasi Motivasi Kerja pada Mahasiswa Universitas Sebelas Maret - Hulwa Anindya Pratiwi; Mintasih Indriayu; Dewi Kusuma Wardani (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2024)
This study aims to determine the effect of entrepreneurial behavior and organizational activity on the work readiness of students from the faculty of teacher training and education at the University of Eleven March 2018 with work motivation as a moderator. Determination of the research method is descriptive quantitative with research subjects of teaching and science faculty students totaling 326 respondents. The sampling technique is random sampling by distributing questionnaires or questionnaires. The data analysis technique used in this research is Moderated Regression Analysis (MRA). The results obtained indicate that: (1) Entrepreneurial behavior has a significant effect on job readiness for FKIP UNS students. (2) Organizational activity has a significant effect on job readiness for FKIP UNS students. (3) Work motivation can moderate the influence of Entrepreneurial Behavior on work readiness for FKIP UNS students. (4) Work motivation can moderate the effect of organizational activity on work readiness for FKIP UNS students.